ANALYZING DETERMINANTS OF REVENUE EXPANSION IN TANZANIAN AND NIGERIAN COMPANIES: A COMPARATIVE ANALYSIS USING WORLD BANK ENTERPRISE SURVEY DATA - Okeke, Charles (Ayden International Journal of Banking, Finance and Technology, 2024)
This paper investigates the impact of contingent and institutional factors on firm revenue growth in Tanzania. Using the World Bank enterprise survey data from 2006 and 2013, we employ the Pooled Ordinary Least Square model to analyze the effects of competition, small size, corruption, female ownership, government regulations, tax rates, access to finance, and skilled workforce on the revenue growth of Tanzanian firms. Our findings show that contingent factors, such as competition, small size, and corruption, have a positive impact on revenue growth, while institutional factors, such as female ownership, government regulations, tax rates, access to finance, and skilled workforce, also play a significant role in driving firm growth. We recommend that the government review regulations for firms' operations and financial institutions provide loans to service firms to boost their liquidity, ultimately improving their revenue. Additionally, firms should prioritize recruitment policies that enable them to hire skilled workers. This study provides updated insights into the factors that influence revenue growth in Tanzanian firms and contributes to the literature on firm growth in developing countries.